Identification of necroptosis-associated mRNA biomarkers in kidney clear cell carcinoma - Zhang, Xiaobo; Jin, Qiaoying; Cheng, Gafang; Niu, Haiyu; Yang, Suping; Chen, Shicheng (Frontiers in Immunology, 2025)
IntroductionKidney clear cell carcinoma (KIRC) is the most common subtype of renal malignancy with a high mortality rate. It is difficult to treat and often leads to death due to its genomic heterogeneity, metastatic nature, and limited effectiveness of targeted and immunotherapies. Recent studies showed that the progression of KIRC is frequently accompanied by significant changes in necroptosis while these studies were limited by small gene sets, which increases the risk of missing low-expressed yet important genes.MethodsThis study focused on necroptosis-associated genes within the context of KIRC and performed a complete closed-loop studies by gene screening, gene expression analysis, model validation and experimental translation.ResultsAmong screened nine core biomarkers (RIPK1, RIPK3, MLKL, CASP8, ZBP1, TLR3, PYGL, TRPM7, PGAM5), CASP8 and TRPM7 were identified as new potential biomarkers. The predictive performance of risk prognostic model for 5-year survival (AUC: 0.77 and 0.89 in training and independent/external validation cohort) outperformed prior studies by 5.5% and 17.1%, respectively. A more pronounced immune response was found with high-risk cohort, underscoring the immunosuppressive properties of tumor immune microenvironments, which evidenced by increased immune cell infiltration and elevated immunogenicity. Drug sensitivity analysis revealed that doxorubicin could serve as a promising therapeutic agent for KIRC. Furthermore, BFTC909 and CAL54 were identified as the most suitable cell lines for in vitro experimental translation, and highlighting three functionally significant target genes (CASP8, PGAM5, and CPT2).ConclusionThis study offers multi-dimensional data that support novel mechanistic investigations and provide valuable insights for developing precision immunotherapy strategies in KIRC.